Foreword from Handling Editor – 11th Edition - Rahmawati, Salfia (ASEAN Journal of Community Engagement, 2022)
We are delighted to present the 11th edition of AJCE, published in July 2022. We have selected ten of the best articles for this edition, consisted of Research Articles and Case-based Articles.